Analysis of the Effects of Social Media on Children Education Mechanisms - Setiawan, Rony; Aprillia, Ariesya; Tjahyadi, Rully Arlan; Lu, Cen; Nursalin, Kezia Kurniawati; Abednego, Felicia; Vaher, Kristina (Aptisi Transactions On Technopreneurship (ATT), 2025)
The increasing use of social media has significantly influenced various aspects of daily life, including children's education mechanisms. This research aims to explore the impact of social media on educational processes and how it shapes learning outcomes for children. The objective of this study is to examine the relationship between social media usage and children's educational development, using SmartPLS analysis as the primary method. By analyzing data collected from students, parents, and educators, the study identifies key factors such as engagement, content accessibility, and social interaction that mediate this relationship. The results reveal that while social media can serve as an effective educational tool, it also presents potential risks, including distraction and exposure to inappropriate content. The findings suggest that balanced usage of social media can enhance children's learning experiences if properly managed. The conclusion underscores the need for further research into the educational implications of social media, emphasizing the importance of parental involvement and regulatory frameworks in ensuring its positive impact on children's education.